Targeted and untargeted lipidomics of Emiliania huxleyi viral infection and life cycle phases highlights molecular biomarkers of infection, susceptibility, and ploidy - Hunter, Jonathan E.; Frada, Miguel J.; Fredricks, Helen F.; Vardi, Assaf; Van Mooy, Benjamin A. S. (Frontiers in Marine Science, 2015)
Marine viruses that infect phytoplankton strongly influence the ecology and evolution of their hosts. Emiliania huxleyi is characterized by a biphasic life cycle composed of a diploid (2N) and haploid (1N) phase; diploid cells are susceptible to infection by specific coccolithoviruses, yet haploid cells are resistant. Glycosphingolipids (GSLs) play a role during infection, but their molecular distribution in haploid cells is unknown. We present mass spectrometric analyses of lipids from cultures of uninfected diploid, infected diploid, and uninfected haploid E. huxleyi. Known viral GSLs were present in the infected diploid cultures as expected, but surprisingly, trace amounts of viral GSLs were also detected in the uninfected haploid cells. Sialic-acid GSLs have been linked to viral susceptibility in diploid cells, but were found to be absent in the haploid cultures, suggesting a mechanism of haploid resistance to infection. Additional untargeted high-resolution mass spectrometry data processed via multivariate analysis unveiled a number of novel biomarkers of infected, non-infected, and haploid cells. These data expand our understanding on the dynamics of lipid metabolism during E. huxleyi host/virus interactions and highlight potential novel biomarkers for infection, susceptibility, and ploidy.